Caracterización morfométrica y reproductiva (hibridación) de siete poblaciones de Artemia franciscana en México, en relación a su hábitat y latitud - Castro Mejía, Jorge (Universidad Autónoma Metropolitana, 2004)
El análisis de las características biológicas específicas de cada población de Artemia permite evaluar, desde el punto de vista evolutivo, la gama de respuestas de la especie y de las poblaciones a un ambiente en particular y sus consecuencias, por ejemplo, la diferenciación morfométrica y el aislamiento reproductivo. En este trabajo se caracterizan a siete poblaciones de A. franciscana con base a su morfometría e hibridación, considerando en si misma a la ubicación de cada una de las poblaciones, así como su interrelación con la latitud y el hábitat. Se determinó la morfometría de los estadios quiste, embrión, nauplio y adulto (machos y hembras), con la ayuda de un microscopio estereoscópico, con cámara integrada a un programa autoanalizador de imágenes. De cada estadio se tomaron 100 individuos. Las poblaciones fueron separadas por el tipo de hábitat que ocupan (costero o agua interior), y por la latitud geográfica (norte, centro y sur). Los datos fueron analizados estadísticamente: primero, por un análisis de varianza (ANDEVA) para determinar diferencias significativas (P<0.05); segundo, un contraste de medias múltiples usando la prueba de Tukey; tercero, una comparación por hábitat y latitud por medio de la técnica de contrastes. Con los valores morfométricos de los adultos, se consideró realizar una disminución de las variables por medio de la técnica de componentes principales. Asimismo, se procedió a realizar un análisis discriminante para separar a las poblaciones. Para ello se utilizó el paquete estadístico SYSTAT 9.0. Para determinar problemas de especiación, se realizaron intercruzas entre las poblaciones y así determinar la producción de F1 y F2. Los quistes con mayor diámetro son los de SLP (292.32 mm) y el más pequeño es YAV (229.20 mm). El diámetro mayor de embrión descapsulado fue para la población de JUCH (258.91 mm) y el menor para YAV (211.67 mm). El quiste con un grosor de corion más grande fue para R.SAL (9.98 mm) y el más pequeño para SLP (6.43 mm). Los nauplios más grandes fueron para C.CIEN (472.41 mm) y los más pequeños para OHUI (379.70 mm). Las poblaciones se discriminan principalmente por la variable del embrión descapsulado y no presentan una separación significativa por hábitat y latitud. El análisis de componentes principales señaló que todas las variables, tanto de machos como de hembras adultas, son importantes y deberán ser incluidas en el análisis discriminante. En cuanto a los valores de las hembras adultas, la población de JUCH presentó los más altos en todas las variables morfométricas; el valor más pequeño se distribuye en todas las poblaciones. Los machos más grandes, al igual que las hembras, son los de JUCH, mientras que los más pequeños son YAV, TEX y R.SAL. Todas las poblaciones presentaron diferencias significativas en cuanto al hábitat y la latitud. En ambos casos se forman tres grupos: el primero formado por las poblaciones TEX, OHUI y YAV; el segundo por SLP, R.SAL, C.CIEN y el tercero, formado solamente por la población de JUCH. Las poblaciones mexicanas presentan problemas de intercruza cuando se hibridizan poblaciones costeras con aguas interiores. Existen problemas de éxito reproductivo debido principalmente a problemas prereproductivos, ya que ni siquiera existe un apareamiento entre las parejas. Por todo lo anterior, podemos concluir que las poblaciones mexicanas de Artemia, se encuentran en un proceso evolutivo de aislamiento reproductivo, que es la especiación, ocasionado por la adaptación de cada una de las poblaciones a su hábitat específico, el cual a impreso esta característica en el genotipo de las poblaciones, ocasionando problemas pre y postcopulatorios en los organismos, así como diferencias morfológicas en cuanto a la longitud total de las hembras con respecto a la longitud del abdomen del macho. Podemos asegurar que aunque las poblaciones no están totalmente separadas genéticamente, ya que existe un bajo éxito reproductivo en la mayoría de las cruzas, así como una baja viabilidad de los híbridos producidos, si se están dando la evolución de barreras genéticas que a la larga darán como consecuencia una especiación entre ellas, así como la tendencia a formar nuevas especies, sobre todo en aquellas en donde la composición iónica del agua es diferente al cloruro de sodio, como lo son las poblaciones de aguas interiores (C.CIEN, SLP. Y TEX).; The specific characteristics of biological analysis of each Artemia population allows the evaluation, from the evolutionary point of view, the range of particular habitat answers of one strain to an specific environment, like the morphometric differentiation and isolation reproduction. In this work seven Artemia franciscana strains were morphometric and reproductive characterized, as well as their interrelation with the latitude and the hábitat type. Cysts, embryos, nauplii and adult (males and females) stage were morphometrical with a stereoscopic microscope, with digital camera integrated to a PC computer with a image autoanalyzer program. One hundred individuals were taken for the measures. The populations were separated by latitude (north, central and south) and habitat type (coastal or inland waters). The statistic analysis were: first, to determinate significance difference (P<0.05) in the strains and (ANOVA); second, an average multiple contrast using the Tukey test; third, an habitat and latitude comparison using the average contrasts thechnique. With the adults morphometric values, it carries out, first an average components technique to decrease the variables number and put it in a discriminant analysis. For all these measures, was used it the statistical package SYSTAT 9.0. To determine especiatión problems, it was carried out an interbreeding experiment with all Artemia mexican strains to obtain and F1 and F2 reproductive production. SLP (292.32 µm)has the biggest cyst diameter and YAV (229.20 µm) has the smallest. The bigger diameter of decapsulated embryo was for JUCH (258.91 µm) population and the minor for YAV (211.67 µm). The bigger thickness chorion was for R.SAL (9.98 µm) and the smallest for SLP (6.43 µm). The biggest nauplii was for C.CIEN (472.41 µm) and the smallest for OHUI (379.70 µm). All populations are principaly discriminated by the decapsulated embryo and they don't show a significant habitat and latitude separation. The average component technique, shows that all adult morphometrical variables (male and female), were important in need to included in the discriminant analysis. For adult females, JUCH has highest values in all the morphometrical data; the smallest values wer distributed in all other populations. For data males, the biggest ones are those of JUCH, while the smallest are for YAV, TEX and R.SAL strains. All the populations shows significant differences in habitat and latitude relationship. In both cases (latitude and habitat), three groups are formed: first one, with TEX, OHUI and YAV populations; second, with SLP, R.SAL, C.CIEN and third, only with JUCH strain. The interbreeding studie shows that the Mexican populations present reproductive isolation between coastal and inlandwaters populations. The low reproductive success in the interbreeding experiment shows prereproductive and postreproductive problems. The mayor problem in the prereproductive phase, is the abscence of couple mating and in the postreproductive phase, is the low survival of the produced hybrid. For all above discuss, it is possible to conclude that the Mexican Artemia are found it, in an evolutionary process of reproductive isolation that is called speciation. This speciation is caused by the adaptation of each population to their specific physicochemical habitat characteristics and printed this information in the genotype of each population, that was determined the pre and post reproductive problems in the different Mexican Artemia strains. Another important thing to considerate, were the relation of the morphometrical differences in total length of the females, with regard to the male abdomen length. I can assure, although that the Mexican populations, are not completely separate genetically, the low reproductive success in most crosses and a produced low viabilityThe average component technique, shows that all adult morphometrical variables (male and female), were important in need to included in the discriminant analysis. For adult females, JUCH has highest values in all the morphometrical data; the smallest values wer distributed in all other populations. For data males, the biggest ones are those of JUCH, while the smallest are for YAV, TEX and R.SAL strains. All the populations shows significant differences in habitat and latitude relationship. In both cases (latitude and habitat), three groups are formed: first one, with TEX, OHUI and YAV populations; second, with SLP, R.SAL, C.CIEN and third, only with JUCH strain. The interbreeding studie shows that the Mexican populations present reproductive isolation between coastal and inlandwaters populations. The low reproductive success in the interbreeding experiment shows prereproductive and postreproductive problems. The mayor problem in the prereproductive phase, is the abscence of couple mating and in the postreproductive phase, is the low survival of the produced hybrid. For all above discuss, it is possible to conclude that the Mexican Artemia are found it, in an evolutionary process of reproductive isolation that is called speciation. This speciation is caused by the adaptation of each population to their specific physicochemical habitat characteristics and printed this information in the genotype of each population, that was determined the pre and post reproductive problems in the different Mexican Artemia strains. Another important thing to considerate, were the relation of the morphometrical differences in total length of the females, with regard to the male abdomen length. I can assure, although that the Mexican populations, are not completely separate genetically, the low reproductive success in most crosses and a produced low viability of the hybrid ones, lead to an evolution of genetic barriers that they will give us, an speciation among them in a “short time”, as well as the tendency to form new species, mainly in those habitats where the ionic composition of the water is different to the sodium chloride, like inland water Mexican populations (C.CIEN, SLP. and TEX).